More Than Just A Visit: Holistic Pastoral Study of Church Pastoral Services for Families of Inmates - Joneldra Karla Tutupary; Daniel Susanto; Nancy Souisa (Program Pascasarjana UKIM, 2025)
The family of inmates is defined as family members who are directly affected by the imprisonment of their family members, who are dependents of the inmates. This study aims to analyze the impact of imprisonment on the families of inmates at the Class III Dobo Penitentiary and develop a holistic pastoral method to support them. Through a qualitative approach, data were collected from in-depth interviews with family members of inmates, pastors, and other related parties, participant observation, and literature studies. The results of the study indicate that imprisonment causes significant emotional impacts, including shame, social isolation, and financial stress. Families often experience stigma from the community, which worsens their psychological condition. This study also highlights the significance of social and spiritual support from the church in helping families navigate challenges. The proposed holistic pastoral care method includes pastoral conversations for adults and children, the formation of support groups, along with other empowerment actions for the families of inmates. With this approach, it is hoped that the families of the inmates can find hope, recovery, and rebuild their lives.